Mild Cognitive Impairment or Attention-Deficit/Hyperactivity Disorder in Older Adults? A Cross Sectional Study - Mendonca, Felippe; Sudo, Felipe Kenji; Santiago-Bravo, Gustavo; Oliveira, Natalia; Assuncao, Naima; Rodrigues, Fernanda; Soares, Rejane; Calil, Victor; Bernardes, Gabriel; Erthal, Pilar; Drummond, Claudia; Tovar-Moll, Fernanda; et al. (Frontiers in Psychiatry, 2021)
BACKGROUND. Attention-Deficit/Hyperactivity Disorder (ADHD) is a highly prevalent neurodevelopmental condition, which may be associated with life-enduring cognitive dysfunction. It has been hypothesized that age-related cognitive decline may overlap with preexisting deficits in older ADHD patients, leading to increased problems to manage everyday-life activities. This phenomenon may mimic neurodegenerative disorders, in particular Mild Cognitive Impairment (MCI). This cross-sectional study aims to assess cognitive and behavioral differences between older subjects with ADHD and MCI. METHODS. A total of 107 older participants (41 controls; 40 MCI and 26 ADHD; mean age = 67.60 ± 7.50 years; mean schooling = 15.14 ± 2.77 years; 65.4% females) underwent clinical, cognitive, and behavioral assessments by a multidisciplinary team at the Memory Clinic, D’Or Institute for Research and Education, Rio de Janeiro, Brazil. Mean scores in neuropsychological tasks and behavioral scales were compared across groups. RESULTS. Participants with ADHD showed poorer performances than controls in episodic memory and executive function with large effect-sizes. Performances were comparable between MCI and ADHD for all domains. DISCUSSION. MCI and ADHD in older individuals are dissociated clinical entities with overlapping cognitive profiles. Clinicians ought to be aware of these converging phenotypes to avoid misdiagnosis.